2017
DOI: 10.1002/zaac.201700383
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Aerogels Synthesizd with Cetyltrimethyl Ammonium Bromide (CTAB) as a Catalyst and its Application for CO2 Capture

Abstract: A series of carbon aerogels were synthesized by polycondensation of resorcinol and formaldehyde using cetyltrimethyl ammonium bromide (CTAB) as a catalyst. The structure and properties of carbon aerogels were characterized by X‐ray diffraction (XRD), Raman, scanning electron microscope (SEM), Fourier transform infrared spectroscopy (FT‐IR), and N2 adsorption‐desorption technologies. Besides, the CO2 capture behavior of carbon aerogels was also investigated. It was found that the amount of CTAB affected the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…These results confirmed again that the laboratory made monolithic hierarchical cryogels from PMF resin presents high porosity, super surface area, and heteroatom nitrogen content, which is much surpassed than the carbon aerogels, cryogels, and xerogels from open literatures due probably to the more stable structure and optimized experiment conditions. More importantly than all these is that the laboratory made carbon cryogel also reveals high-performance of mechanical properties, which is rarely mentioned in the open literatures. ,, Furthermore, the CO 2 capture performance was also compared with carbon gels, ,,,,, activated carbon gels, ,, commercial activated carbons, and also N-doped carbon materials, ,,, and it was found that the CO 2 adsorption capacities of PMF carbon cryogels were among the highest ever reported for carbon aerogels, cryogels and aerogels. It must be noted that the capacities also surpassed to those of activated carbon gels (ACG), commercial carbon materials, while are at a high level among these N-doped carbon materials.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…These results confirmed again that the laboratory made monolithic hierarchical cryogels from PMF resin presents high porosity, super surface area, and heteroatom nitrogen content, which is much surpassed than the carbon aerogels, cryogels, and xerogels from open literatures due probably to the more stable structure and optimized experiment conditions. More importantly than all these is that the laboratory made carbon cryogel also reveals high-performance of mechanical properties, which is rarely mentioned in the open literatures. ,, Furthermore, the CO 2 capture performance was also compared with carbon gels, ,,,,, activated carbon gels, ,, commercial activated carbons, and also N-doped carbon materials, ,,, and it was found that the CO 2 adsorption capacities of PMF carbon cryogels were among the highest ever reported for carbon aerogels, cryogels and aerogels. It must be noted that the capacities also surpassed to those of activated carbon gels (ACG), commercial carbon materials, while are at a high level among these N-doped carbon materials.…”
Section: Resultsmentioning
confidence: 98%
“…Several bands near 2922 cm –1 can be identified as aliphatic C–H stretching vibrations. In fact, with different dilution ratios and degrees of cross-linking per unit volume, the peaks at some wavenumbers should be different, but this difference was not observed clearly. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our previous work, we have prepared a serious of additional carbon aerogels by regulating the dosage of catalyst and the solution concentration of precursors were used for CO 2 capture. The data selecting and analysis process were elaborated in the supporting information.…”
Section: Resultsmentioning
confidence: 99%
“…Structure manipulation was the important method to enhance CO 2 adsorption performance. In addition, the amount of catalyst [11] and doped nitrogen [12] in the preparation process of carbon aerogels were crucial to pore volume and surface defect, thus affecting its CO 2 adsorption behavior. Post-modification of carbon aerogels [13] by adding amine was another effective measure to modulate its CO 2 adsorption performance.…”
Section: Introductionmentioning
confidence: 99%